Impacts of Zero Punishment on Student’s Behavior and Classroom Learning at Government Primary Schools - Swera Latif; Islam, Md. Ramizul; Saeed, Sana (CenRaPS Journal of Social Sciences, 2020)
The aim of this study is to identify the impacts of zero punishment on student’s behaviour and classroom learning at government primary schools. This study was conducted at city Faisalabad of Pakistan. The target population was primary school teachers in the city. The sample of 106 was selected by using online sampling calculator www.surveysystem.com with confidence level 95% and interval level 8. By applying the simple random sampling technique the data were collected from the respondents through a well-developed questionnaire. The Statistical Package for Social Sciences (SPSS) was used to analyses the collected data and results were discussed for the findings. The study findings reveal that zero punishment have good positive impacts on student’s behaviour and classroom learning. The result is also observed that physical punishment has negative effects on the students like as they may stop from school or may fall in depression, fear and hatred. Zero punishment treats to encourage to learning and behave polite each other in the school. So teachers should ask pupils questions with politeness in the classroom to improve student learning and should be cooperative for student. Students should be motivated to participate in classroom activities with caringly. Teachers were expected to be lenient and not intimidate students into corporal punishment.